Genesis Of The Development Of Contractual Legal Relations Of Medical Services (Eurasian Journal of Humanities and Social Sciences, 2024)
The article analyzes issues related to the genesis of the development of medical service contractual legal relations. Also, the issues of the Tsarist period of Tsarist Russia, the prosperity of Medicine in Turkestan were analyzed on the basis of educational archival sources and First-Class sources.